William Allen White’s Prairie - Thomas Fox Averill (Symphony in the Flint Hills, 2012)
William Allen White called himself a prairie town boy, and he celebrated the prairie in his writing. From his earliest fiction, The Real Issue (1896), to his final novel, In the Heart of a Fool (1918), to his Autobiography (1946), White’s natural world is the Kansas he grew up in and loved as “the fairest of the world’s habitations.”
Keywords: William Allen White; prairie; poem; stories; El Dorado; literature; Emporia; Kansas State Teachers College; words; wood; barn; Flint Hills; wonder; landscape; grassland; woodland; wild; heritage; beauty; preserve; past